Valorizing date seeds through ultrasonication to enhance quality attributes of dough and biscuit: Part 2 – Study on bioactive properties, sensory acceptance, in vitro gastrointestinal digestion and shelf life of biscuits - Meththa Ranasinghe; Mariam Alghaithi; Constantinos Stathopoulos; Balan Sundarakani; Sajid Maqsood (Ultrasonics Sonochemistry)
Aligning with sustainable food system development, in this study, date seeds derived compounds were utilized as functional ingredient to formulate value-added biscuits. Ultrasound-assisted extraction (UAE) was employed as a non-thermal method to extract polyphenolic compounds from small, medium and large particles of defatted date seed powder (DDSP). The remaining fiber-rich fraction (residue) was further utilized. Water content in biscuit formulation was replaced by the extract, and the fiber-rich fraction was substituted at three substitution levels; 2.5 %, 5 % and 7.5 %. Effects of baking on bioactive properties of dough, nutrient composition, sensory analysis, bioaccessibility of polyphenols, and shelf-life of biscuits were analyzed. Total phenolic content (TPC) increased in dough and biscuit with incorporated fiber-rich fraction. TPC of dough decreased with increasing particle size of fiber-rich fraction while biscuits exhibited an opposite trend. Similar tendency was observed with antioxidant activity of dough and biscuit. TPC was higher in biscuits than dough, with the highest values of 0.46 mg gallic acid equivalents (GAE)/g and 2.26 mg GAE/g in dough and biscuit, respectively. Fiber and moisture contents in biscuits increased while protein content decreased with fortification. Consumers showed moderate acceptance of fortified biscuits with overall acceptability comparable with the control biscuits. Bioaccessibility index of polyphenols upon gastrointestinal digestion was high in biscuits with 5 % and 7.5 % substitution of small and medium sized particles of fiber-rich fraction. Phenolic retention increased with fiber fortification and at the end of 6 months the lowest thiobarbituric acid reactive substances (TBARS) value of 18.23 nmol malondialdehyde (MDA)/g sample, was observed in 7.5 % large particle substituted biscuit. Thus, utilizing date seeds in the form of green extracted polyphenols and fiber-rich fraction, as functional and bioactive ingredients highlight sustainable processing and utilization of date-fruit processing by-products which is in line with the circular economy approach.